Consideration of treatment goals and termination algorithm for adolescent atopic dermatitis using upadacitinib - Takeshi Koga; Takeshi Koga; Takeshi Koga; Keisuke Okada; Keisuke Okada; Takahiro Shimizu; Takahiro Shimizu; Eiji Morita; Eiji Morita; Toshiko Itazawa; Toshiko Itazawa (Frontiers Media S.A., 2024)
ObjectivesStandardized criteria for disease activity and end of treatment of systemic treatment of atopic dermatitis have not been established. The objective of this study is to explore the experience using upadacitinib retrospectively, to find clues to weaning from systemic treatment, and to determine the algorithm for setting treatment goals and terminating systemic treatment.MethodsFourteen patients treated with upadacitinib between 1 November 2021 and 31 December 2023 were enrolled in the study. Topical anti-inflammatory treatments were combined. Treatment outcomes were established according to the European Task Force of Atopic Dermatitis guidelines. To evaluate disease status and control, we adopted the Treat to target strategy. Changes in serum biomarkers (TARC and IgE) were also observed.ResultsAll patients achieved EASI 50 after 52 weeks. At 76 weeks, 80% and 30% of patients achieved EASI 75 and EASI 90, respectively. Four patients completed upadacitinib, five patients discontinued treatment, and five patients remained on treatment. Two patients achieved complete remission without topical anti-inflammatory treatment. Two patients discontinued due to adverse events. Patients with better treatment adherence, mainly topical treatment, tended to be able to withdraw from UPA. IgE increased from baseline in 11 patients (78.6%) and TARC increased in 14 patients (100%). These biomarkers decreased from the peak 24-48 weeks after initiating treatment, after the improvement of eczema.ConclusionCombining systemic and topical treatments effectively induces remission in AD patients. Transitioning off systemic treatment begins by achieving remission maintained solely with topical therapy, emphasizing the importance of adherence.